2017
DOI: 10.1159/000479120
|View full text |Cite
|
Sign up to set email alerts
|

Early Rebleeding after Brain Arteriovenous Malformation Rupture, Clinical Impact and Predictive Factors: A Monocentric Retrospective Cohort Study

Abstract: Background: Brain arteriovenous malformations (BAVMs) are a leading cause of intracranial hemorrhage in young adults. This study aimed to identify individual predictive factors of early rebleeding after BAVM rupture and determine its impact on prognosis. Methods: Early rebleeding was defined as a spontaneous intracranial hemorrhage within 30 days of BAVM rupture in patients with nonobliterated BAVMs. One hundred fifty one patients with 158 BAVM hemorrhagic events admitted to a tertiary care center during 14 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
0
9
0
3
Order By: Relevance
“…In this study, early rebleeding failed to reach statistical significance in its association with S100B secondary increase. A previous study [5] found that early rebleeding was associated with poor neurological outcome but not with in-hospital mortality, and could suggest that rebleeding may not be responsible for sufficient brain cell damage to release S100B protein in the serum, unlike infarction. The low rate of secondary infarction could underpower its effect on in-hospital mortality and thus explain the lack of significance.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In this study, early rebleeding failed to reach statistical significance in its association with S100B secondary increase. A previous study [5] found that early rebleeding was associated with poor neurological outcome but not with in-hospital mortality, and could suggest that rebleeding may not be responsible for sufficient brain cell damage to release S100B protein in the serum, unlike infarction. The low rate of secondary infarction could underpower its effect on in-hospital mortality and thus explain the lack of significance.…”
Section: Discussionmentioning
confidence: 93%
“…Markers of initial severity following BAVM rupture as well as long-term outcome have been widely studied [1,[7][8][9]. In contrast, studies evaluating the impact of early complications (and their incidence) such as rebleeding or ischemia remain scarce [5,6,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recurrence of hemorrhage may also be one among the various causes for aneurysm rupture without SAH [ 6 ]. The possible mechanism may be due to protein deposition occurring around the rupture of aneurysm after the initial bleeding form a fibrinous adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Hal ini menimbulkan gejala pendarahan akibat rupturnya hubungan tersebut, [1][2] membuat MAV sebagai penyebab pendarahan intraserebral nontraumatik terbanyak pada usia <35 tahun dengan insiden sekitar 1:200.000 orang setiap tahunnya. 3 Pendarahan pada MAV dihubungkan dengan mortalitas dan morbiditas yang signifikan, serta beban biaya kesehatan selama terapi. 4 Masalah pada MAV adalah risiko untuk pendarahan berulang, antara lain pada lokasi di batang otak atau infratentorial.…”
Section: Pendahuluanunclassified